Proteomic and phosphoproteomic analyses of chromatin‐associated proteins from Arabidopsis thaliana. Issue 19 (10th July 2014) - Bigeard, Jean; Rayapuram, Naganand; Bonhomme, Ludovic; Hirt, Heribert; Pflieger, Delphine; Vondriska, Thoms M.; Jensen, Ole N.
<x xml:space="preserve">Abstract</x> The nucleus is the organelle where basically all DNA‐related processes take place in eukaryotes, such as replication, transcription, and splicing as well as epigenetic regulation. The identification and description of the nuclear proteins is one of the requisites toward a comprehensive understanding of the biological functions accomplished in the nucleus. Many of the regulatory mechanisms of protein functions rely on their PTMs among which phosphorylation is probably one of the most important properties affecting enzymatic activity, interaction with other molecules, localization, or stability. So far, the nuclear and subnuclear proteome and phosphoproteome of the model plant Arabidopsis thaliana have been the subject of very few studies. In this work, we developed a purification protocol of Arabidopsis chromatin‐associated proteins and performed proteomic and phosphoproteomic analyses identifying a total of 879 proteins of which 198 were phosphoproteins that were mainly involved in chromatin remodeling, transcriptional regulation, and RNA processing. From 230 precisely localized phosphorylation sites (phosphosites), 52 correspond to hitherto unidentified sites. This protocol and data thereby obtained should be a valuable resource for many domains of plant research.